Multigenerational travel: a narrative review of family-oriented tourism trends and implications - Ahmad Harnaini @ Abdullah, Nor Hayati; A Jamal, Salamiah; Amir, Ahmad Fitri; Nordin, Mohammad Ridhwan (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
Multigenerational family travel has become a significant trend in contemporary tourism. This type of travel, involving grandparents, parents, and children, reflects evolving family structures and the growing importance of shared experiences in fostering familial bonds. Despite its increasing relevance, research on multigenerational travel remains limited. This narrative review synthesizes existing literature to explore key aspects such as motivations, benefits, decision-making, challenges, and industry responses to multigenerational travel. By providing a comprehensive analysis, this study aims to address the gap in the literature and offer insights for future research and industry stakeholders.